EXPERIMENTAL STUDY ON THE PRETENSION FORCE OF MULTI-BOLTED STRUCTURE - GUO LiLun; CHEN ZhongFu; LUO JingRun (Jixie qiangdu)
The pre-tension force of a multi-bolted structure under pure tightening torque is studied by experimental methods. Firstly,Experiment for single bolted structure is implemented,whose pretension force is obtained by strain gauge method. It shows that this pretension force measurement method is reasonable by comparing the experimental results and the theoretical results. On this basis,the experiment for multi-bolted structure is operated. The results shows that its pretension force is lower than the single bolted structure,and its value is relating to the pretension state of the bolt. When the pretension state is stable,its pretension force is about 0. 6 times of the single bolted.